MUSIK DANGDUT: SUATU KAJIAN BENTUK MUSIK - Aesijah, Siti (Harmonia: Journal of Arts Research and Education, 2010)
This study aims to describe the form of dangdut music. The results are expected to be useful to provide information about the form of dangdut music and can be used as a theoretical contribution to the next research. This research using descriptive analysis method with musicological approach. Data was collected through observation and documentation techniques. The results showed that the dangdut music/song is form of musical composition. As a rule of a composition, judging from its shape, the dangdut music as a composition that is composed of essential and auxiliary components. The essential components of dangdut music shaped by the pattern of three sections A-A’-B-A’, while the auxiliary components consists of an introduction, interlude, and coda. In the presentation, dangdut music composition is presented with the pattern: introduction-A-A’-interlude-B-A’-Coda. Kata kunci: musik dangdut, bentuk musik